Generalized Aggregate Operators on Neutrosophic Hypersoft Set - Rana Muhammad Zulqarnain; Xiao Long Xin; Muhammad Saqlain; Florentin Smarandache (Neutrosophic Sets and Systems, 2023)
Multi-criteria decision making (MCDM) is concerned about coordinating as well as looking after selection as well as planning problems which included multi-criteria. The neutrosophic soft set cannot handle the environment which involved more than one attribute. To overcome those hurdles neutrosophic hypersoft set (NHSS) is defined. In this paper, we proposed the generalized aggregate operators on NHSS such as extended union, extended intersection, OR-operation, AND operation, etc. with their properties. Finally, the necessity and possibility operations on NHSS with suitable examples and properties are presented in the following research.